2003
DOI: 10.1117/12.479757
|View full text |Cite
|
Sign up to set email alerts
|

Lasing in disordered media

Abstract: We review our recent work on lasing in active random media. Light scattering, which had been regarded detrimental to lasing action for a long time, actually provided coherent feedback for lasing. We also trapped laser light in micrometer-sized random media. The trapping was caused by disorder-induced scattering and interference. This nontraditional way of light confinement has important application to microlasers. The threshold of ranodm laser can be reduced by incorporating some degree of order into an active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 121 publications
0
17
0
Order By: Relevance
“…Random lasers (RLs) are light sources that can generate nearly coherent light with the use of scattering media with gain [1][2][3][4][5][6]. As the optical feedback for lasing is provided by the multiple scattering of light instead of well-defined cavities, the random spatial distribution of the refractive index in the media directly affects the random lasing action.…”
Section: Introductionmentioning
confidence: 99%
“…Random lasers (RLs) are light sources that can generate nearly coherent light with the use of scattering media with gain [1][2][3][4][5][6]. As the optical feedback for lasing is provided by the multiple scattering of light instead of well-defined cavities, the random spatial distribution of the refractive index in the media directly affects the random lasing action.…”
Section: Introductionmentioning
confidence: 99%
“…Cold and ultra-cold atomic ensembles are currently of significant interest for a wide range of practical applications in metrology, development of frequency standards, the possibility of cold-atom based random lasing [1][2][3][4][5], and quantum information science [6][7][8][9][10][11][12][13][14]. The efficacy of such practical applications depends substantially on the optical thickness of these ensembles.…”
Section: Introductionmentioning
confidence: 99%
“…The path length over which a photon travels before generating another photon is defined as the generation length (l gen ) and it is approximated to the gain length (l g = path length over which the light intensity is amplified by a factor of e) [236]. Once this gain length equals to the average path length (l pat = average distance that a photon travels before leaving the medium), the number of photons increase rapidly [236]. Mathematically, it is shown that the solution to the diffusion equation, including optical gain, increases exponentially [237].…”
Section: Chapter 4 Zno Random Lasersmentioning
confidence: 99%
“…Mathematically, it is shown that the solution to the diffusion equation, including optical gain, increases exponentially [237]. At this threshold condition, a critical volume (V th ) is hypothesized by the relation [236], to a rapid increase of photons at these wavelengths [238].…”
Section: Chapter 4 Zno Random Lasersmentioning
confidence: 99%
See 1 more Smart Citation